Pemikiran Ibnu Taimiyah Mengenai Upah yang Setara dan Relevansinya Terhadap Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Al-Rasyid, Camelia Sofwan; Witro, Doli; Ayu, Dena (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This article discusses Ibn Taimiyah’s thoughts on equal wages and their relevance to Law Number 13 of 2003 concerning Manpower. Ibnu Taimiyah argues that in economic transactions, there must be justice, all contracts must be based on the ability of all parties to agree, including in terms of workers' wages. According to Ibn Taimiyah's view, the concept of equal wages is when wages between workers and employers are determined from bargaining between the two parties. In Law Number 13 of 2003 concerning Manpower, the provisions regarding wages are discussed in articles 88 and 89, and it is stated that every worker has the right to receive wages for a decent life. This study describes Islamic economic thought according to Ibnu Taimiyah about equal wages and how it is relevant to wages in the provisions of Law Number 13 of 2003 concerning Manpower. The method used is a qualitative research method. The data obtained are presented and described into a relevant analysis to conclude from the exposure of the two concepts. The analysis results show that the concepts of equal wages and wages in Law Number 13 of 2003 concerning Manpower both determine wages for workers. In the concept of equal pay, if wages are not specified in the contract, the wages allocated are commensurate through clear wage standards or the usual wages for the job. Entering Law Number 13 of 2003, the existing wages can be equated with the minimum wage as regulated in Article 88.